2009
DOI: 10.4149/neo_2009_01_40
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin truncation and Sialyl Lewis-X overexpression in oral squamous cell carcinoma and oral precancerous conditions

Abstract: The present study aimed to determine significance of E-cadherin, a cell adhesion molecule, and sialyl Lewis-X (sLe X ), a cell surface antigen, in oral carcinogenesis. Expressions of E-cadherin and sLe X were detected using western blot analysis from oral malignant (n=25), and oral precancerous tissues (OPC, n=20) and their adjacent normal tissues. An altered expression of E-cadherin (E-cad) and sLe X was observed in malignant and precancerous tissues. E-cad western blot revealed presence of two bands, a 120 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(55 reference statements)
2
11
1
Order By: Relevance
“…The data were consistent with our earlier studies which earlier have reported positive correlation of 97 kDa truncated E-cadherin protein with advanced stage and lymph node metastasis (Shah et al, 2009). Earlier studies have documented E-cadherin in non-tumor epithelium adjacent to oral cancer as a risk marker for the development of multiple tumors (Zhou et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…The data were consistent with our earlier studies which earlier have reported positive correlation of 97 kDa truncated E-cadherin protein with advanced stage and lymph node metastasis (Shah et al, 2009). Earlier studies have documented E-cadherin in non-tumor epithelium adjacent to oral cancer as a risk marker for the development of multiple tumors (Zhou et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the reduction in E-cadherin expression with increasing severity of histopathological dysplasia grading was also observed. Previous studies have found E-cadherin expression to be significantly reduced in dysplastic oral mucosa and OCSCC [ 8 , 15 , 17 , 18 ], considering that loss of cohesion is one of the key features of dysplasia. Also recently published data by Freitas Silva et al [ 21 ] reinforced our findings by demonstrating E-cadherin downregulation leading to phenotypic changes in early stages of oral carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…33-37 The highly tumorigenic properties of the CSC suggest that they may be the critical population of cancer cells in the development of metastasis, just as they have been proven to be in primary tumor development and growth. 22 Clinically, CSC enrichment is directly linked to tumor recurrence, treatment failure, and metastases in HNSCC (reviewed in 14 ). The role of CSC in the development of metastasis is not yet well understood.…”
Section: Discussionmentioning
confidence: 99%